Supervisi Akademik Kepala Sekolah dalam Meningkatkan Kinerja Guru - Badriyah, Badriyah (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Academic supervision is considered quite urgent in finding bright spots of weaknesses of educational institutions. The findings obtained are the responsibility of education managers to continue to improve in order to create a good educational culture. In this study, it was concluded that the academic supervision carried out at SD Negeri 5 Sumbermulyo was as follows; First, the teacher council meeting, this meeting was held to compile strategic steps and preparations for the implementation of supervision. Workshops or workshops are carried out as an effort to increase the competence of the teacher council and administrative personnel, guided reading, namely facilitating so that reading can run integrated so that it is more effective, bulletin boards by collecting written works related to schools, and field trips through normalization of the environment that has the potential to become tourist attractions